2018
DOI: 10.1002/ccr3.1488
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae as a cause of lactational mastitis: a case report

Abstract: Key Clinical MessagePneumococci are predominant in respiratory tract infections but may have unusual presentations such as lactational mastitis. We report a 29‐year‐old breastfeeding woman with pneumococcal mastitis confirmed by positive blood culture and culture of milk. Previously, a few similar cases have been reported, but none was associated with bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Two cases7 8 showed that an infected child could cause S. pneumoniae mastitis in the mother. Four other cases9–12 suggested an association with S. pneumoniae mastitis, even if the child was asymptomatic. The exact mechanism underlying this infection remains unclear; however, both host and pathogen factors are thought to play a key role 16.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Two cases7 8 showed that an infected child could cause S. pneumoniae mastitis in the mother. Four other cases9–12 suggested an association with S. pneumoniae mastitis, even if the child was asymptomatic. The exact mechanism underlying this infection remains unclear; however, both host and pathogen factors are thought to play a key role 16.…”
Section: Discussionmentioning
confidence: 98%
“…The mean age was 33 years, all seven cases (100%) had immunocompetent status, and both the right and left sides were affected. All seven cases (100%) had a fever over 38°C at the initial presentation, two of seven cases (29%)11 presented with bacteraemia and were associated with septic shock. All seven cases (100%) had a good clinical course with prompt recovery after appropriate antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Debemos destacar dos casos de mastitis lactacional y uno de fascitis necrotizante. La mastitis lactacional neumocócica es excepcional, habiéndose descrito 5 casos desde 1995 [13][14][15]. En todos ellos, S. pneumoniae se aisló en los cultivos de leche materna, y su presencia se atribuyó a la transmisión desde el niño en el momento del amamantamiento.…”
Section: Materials Y Métodosunclassified